EKSISTENSI PERATURAN DAERAH TENTANG PAKAIAN MUSLIM DAN MUSLIMAH DI KABUPATEN BULUKUMBA - Nurjannah, Nurjannah; Hisbullah, Hisbullah (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2023)
This study aims to analyze the implementation of Regional Regulation No. 3 of 2003 concerning Muslim Clothing and Muslim Women in Bulukumba Regency. The type of research used is qualitative research with a normative juridical and normative theological approach. The results showed that formally, Regional Regulation Number 3 of 2003 as the basis for the enforcement of Muslim clothing and Muslim women is still valid today because it has not been revoked, but its existence needs to be evaluated. Because it has been valid for decades, so it needs to be observed whether its existence is still relevant, or needs to be substantially improved by following the times.